Hotel companies and corporate environmentalism - Paul Reynolds (Tourism & Management Studies)
Hotels consume a huge amount of resources in the way of energy and water, and many are built in fragile environments. Despite the strong interest in environmental sustainability, hotel companies have an uneasy relationship with trying to ensure green credentials while pleasing their customers and maintaining competitive advantage. How do hotel companies devise and manage their strategies in their relationship with the natural environment? What are the factors that influence their choice? This paper identifies four important antecedents to corporate environmentalism and examines them within political/economic framework bounded by stakeholder theory. The emergence of environmental issues and the implications for strategy are debated and the theoretical and practical implications of integrating environmental issues into corporate strategies are discussed.